STANDARDIZATION OF GLIGISCIN TABLETS - Tashpulatova, Azizahon D. (International Journal of Psychosocial Rehabilitation, 2020)
The research work states the results of standardization and quality control of Gligiscin tablets. As it is known, the national medicine policy is aimed at reducing the dependence of Uzbekistan’s health care on the import of medicines by full using of its own production capacities, raw materials and scientific and technical potential, developing at the same time its pharmaceutical and medical industry. Based on the pharmaceutical and physiological features of both Zinc and glycyrrhizic acid, a high specific hepatoprotective activity can be expected at their combination. Considering the demandfor creating a new hepatoprotective preparation based on local plant raw materials, particularly glycyrrhizic acid obtained from the Licorice root, a new coordination compound of Zinc with glycyrrhizic acid and histidine has been synthesized, which has hepatoprotective and hypolipidemic properties, conventionally named Gligiscin. The aimand tasks of the research and the further stage of development is to determine chemical and biological safety indicators of Gligiscin tablets in accordance with the General Technical Regulation on Medicines Safety (Annex to the Resolution of CMRUz dated 27.10.2016 for № 365). Materials and methods of research. For determination of quality indicators, the following equipment was used in the process of work: devices Erweka TBH 30and Erweka ZT 44 (Germany2004); tester for determination of solid medicines abrasion TAR 200, Erweka (Germany 2004). Besides, spectrophotometric and photocolorimetric methods were applied on thedevice UV-spectrophotometr 8453 by Agilent Technologies (Germany). Results and their discussion. Standardization of Gligiscin tablets considering chemical and biological safety indicators, such as: average weight and deviation from average weight, degradability, abrasion strength, fracture strength, was performed according to General Technical Regulation on Medicines Safety (Annex to Regulation of CMRUz by №365 dated 27.10.2016). The quality of the produced tablets was determined by such indicators asorganoleptic, physical, chemical, bacteriological and biological. Quality control of ready-made tablets was carried out according to the requirements of pharmacopoeia article "Tablets," as well as private pharmacopoeia articles, by the following indicators: description, authenticity, average weight and deviation from average weight, degradability, abrasion strength, fracture strength, dissolution, microbiological purity, foreignimpurities, quantitative definition. Conclusion. The standardization limits for Gligiscin tablets have been established in accordance with SP XI and SP XII. On the basis of the obtained results, a draft of standard documentation for Gligiscin tablets has been developed. The tested indicators are included into the draft of standard documentation for Gligiscin tablets.